2014
DOI: 10.1038/pr.2014.205
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury and progression of renal failure after fetal programming in the offspring of diabetic rats

Abstract: Background: Diseases of adulthood, such as diabetes and hypertension, may be related to changes during pregnancy, particularly in kidney. We hypothesized that acute kidney injury progresses more rapidly in cases of fetal programming. Methods: Diabetic dams' offspring were divided into: CC (controls, receiving vehicle); DC (diabetics, receiving vehicle); CA (controls receiving folic Acid solution, 250 mg/kg); and DA (diabetics receiving folic acid solution). Renal function tests, morphometry, gene, and protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
2
2
0
1
Order By: Relevance
“…Pearson correlation test showed a significant positive correlation between fibronectin and urea (r 2 = 0.498, p > 0.01) and between fibronectin and creatinine (r 2 =0.356, p>0.05). These results agreed with previous study that found prefibrogenic markers associated positively with creatinine and urea levels in short term induction of renal failure (40) . Interestingly, KIM-1 showed a significant positive correlation with fibronectin (r 2 =0.536, p>0.01).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Pearson correlation test showed a significant positive correlation between fibronectin and urea (r 2 = 0.498, p > 0.01) and between fibronectin and creatinine (r 2 =0.356, p>0.05). These results agreed with previous study that found prefibrogenic markers associated positively with creatinine and urea levels in short term induction of renal failure (40) . Interestingly, KIM-1 showed a significant positive correlation with fibronectin (r 2 =0.536, p>0.01).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, fibronectin ROC analysis recorded an AUC of 0.829 and cut off value of 73.87 ng/ml suggesting a promising predictable biomarker for AKI diagnosis. This data came in line with another study that indicated the prefibrogenic biomarkers can be utilized to predict AKI, increasing the opportunities of more interventions in treatment of renal conditions (40) . It should be mentioned that our study has some limitations.…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to previous, the study of Jin et al (2009) demonstrated that folic acid administered in high doses causes acute renal failure. Significant increases in creatinine and urea levels and decreased renal function were found in the offspring of diabetic progenitors and controls who received folic acid (250 mg/kg) (Corrêa et al 2015). Renal failure caused by folic acid may be induced by the deposition of folic acid crystals, which block the tubules, or D r a f t by direct toxicity of tubular epithelial cells (Gupta et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that exposure to adverse conditions during pregnancy can affect kidney development, leading to a decrease in the number of nephrons, impaired kidney function, and long-term programming for hypertension and chronic kidney disease in adulthood [ 60 ]. These factors include maternal malnutrition, inadequate placental blood supply, gestational diabetes, glucocorticoids, nicotine, alcohol, vitamin A deficiency, and maternal medication exposure (such as angiotensin-converting enzyme inhibitors, antibiotics, phenytoin, antiepileptic drugs, and cyclophosphamide), and their underlying mechanisms have been extensively studied [ [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] ].…”
Section: Altered Renal Mirnas Expression and Abnormal Renal Developmentmentioning
confidence: 99%